2007
DOI: 10.1080/02791072.2007.10399870
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Gamma Hydroxybutyrate (GHB) Ingestion: A Focus Group Study

Abstract: GHB (gamma hydroxybutyrate) is a significant new drug of abuse added to the United States Controlled Substance Act in 2000. The majority of the published literature on GHB consists of clinical case reports, mainly from emergency departments, and a collection of laboratory-based studies, focused mainly on anesthesia. While comments about the various experiences and behaviors of human users are often included in such studies or reports, these aspects of GHB are only just beginning to be systematically investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 28 publications
(29 reference statements)
8
83
0
3
Order By: Relevance
“…Co-ingestion of GHB with other drugs of abuse as a high-risk behavior was determined by the findings of our GHB focus groups, described above (10). This is consistent with other data indicating that drug coingestion with GHB is common (12).…”
Section: Defining Risk Taking Behaviorssupporting
confidence: 91%
See 1 more Smart Citation
“…Co-ingestion of GHB with other drugs of abuse as a high-risk behavior was determined by the findings of our GHB focus groups, described above (10). This is consistent with other data indicating that drug coingestion with GHB is common (12).…”
Section: Defining Risk Taking Behaviorssupporting
confidence: 91%
“…We used a categorical approach to variable characterization, seeking where possible to divide the study group dichotomously consistent with observed distribution. The selection of certain key variables for study inclusion was informed by our earlier analysis of GHB focusgroup discussions we conducted as part of the FORGE study (10). Socio-demographic information garnered from that study indicated that GHB users tend to be predominantly white, older, unmarried (living alone or in non-traditional family arrangements), relatively well-educated, with stable employment, of middle class or high income levels, and with a substantive subset of users that identified as gay or bisexual.…”
Section: Defining Sociodemographic Characteristicsmentioning
confidence: 99%
“…These results support the hypothesis that GHB acts preferentially at the level of the hippocampus to inhibit information processing. The present results may help explain why individuals intoxicated with GHB may not remember specific experiences due to disruptions in hippocampal processing but have intact emotional memories [4,68]. Whether GHB impairs hippocampusbased cognitive functioning in male adolescent rat needs to be investigated.…”
Section: Discussionmentioning
confidence: 87%
“…GHB is abused by a small percentage of the population (< 1%) as a recreational drug in a home setting or as a "club drug" (Sumnall et al, 2008). Unlike certain media reports suggested, the major type of GHB consumer was shown to be well-educated, financially secure and fully employed, living a stable, middle-class urban life (Degenhardt et al, 2002;Barker et al, 2007). In humans, the abuse liability was shown to be comparable to the benzodiazepine flunitrazepam (Abanades et al, 2007) and intermediate between triazolam and pentobarbital (Carter et al, 2006).…”
Section: Subjective Effects Medical Use and Abusementioning
confidence: 99%